Implementation Of A Decision Support System In Determining Recipients Of Rice Seed Aid For Farmers Groups Using Smart Method - Fathan Naufal Rosidin; Yudhi Raymond Ramadhan; Dede Irmayanti (RISTEC : Research in Information Systems and Technology, 2025)
The Purwakarta Regency Food and Agriculture Service plays a crucial role in distributing rice seed aid to farmer groups. However, the process of determining recipients is often time-consuming and not entirely objective. To address this issue, this study developed and built a web-based system that can assist the agency in making decisions quickly and fairly. This system applies the SMART (Simple Multi-Attribute Rating Technique) method, a technique that evaluates and assigns weights to several criteria, such as land area, harvest yield, harvest target, number of group members, and the volume of seeds submitted. The system was developed using the waterfall method, which includes planning, design, construction, and testing. Test results show that this system is capable of providing accurate calculations and assisting the agency in determining aid recipients more easily and transparently. By inputting criteria, sub-criteria, and alternatives from the data obtained using 10 data as samples to display the ranking of farmer groups entitled to receive rice seed assistance, namely the Mekar Jadi farmer group from Tegalwaru sub-district, and Batutumpang village with a final value of 0.7833 as one of the priorities in the distribution of rice seed assistance.